CITRA GURU BIMBINGAN DAN KONSELING DALAM NOVEL DILAN: DIA ADALAH DILANKU TAHUN 1990 KARYA PIDI BAIQ - Kurniawan, Eva Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The teacher is a commendable figure. Guidance and counseling teachers are one of the professions that often deal with students who have problems. The character of a guidance and counseling teacher must be a figure that is accepted in all circles. However, the figure of the guidance and counseling teacher in the novel Dilan: Dialah Dilanku 1990 by Pidi Baiq is not portrayed that way. The image of the guidance and counseling teacher, through a character named Suripto, is depicted with a bad representation or image. This research aims to find out what bad images of guidance and counseling teachers are displayed and in what way this image is conveyed in the story. The method used in this research uses a descriptive analysis approach. The theory used is character characterization theory. The findings obtained show that the image of guidance and counseling teachers is depicted as someone who has bad character, namely carrying out verbal and physical violence, inciting, thinking rigidly and harassing female students. These bad characters are obtained through expository and dramatic characterization patterns. These two patterns of character characterization emerge in showing Suripto's image as a guidance and counseling teacher.